Cerium(III)-Selective Membrane Electrode Based on Dibenzo-24-crown-8 as a Neutral Carrier - Susheel K. Mittal; S. K. Ashok Kumar; Harish K. Sharma (E-Journal of Chemistry)
Cerium(III)-selective membrane electrodes have been prepared using dibenzo-24-crown-8 (DB24C8) as an electroactive material. A membrane having a composition: DB24C8 (4.5%), plasticizer (NPOE, 62.5%) and PVC (33%) gives the best performance. It works well over a wide Ce(III) ion-concentration range of 1x10-5 M to 1x10-1 M with a Nernstian slope of 19.0 mV/decade and a detection limit of 3x10-5 M. It has a fast response time of 20 seconds and has an average lifetime of four months. The internal solution concentration does not have a significant effect on the response of the electrode except for a change in intercept of the calibration curves. The working pH range for Ce(III) solutions (1x10-2 M and 1x10-3 M) is 3.5-8.0. The proposed sensor shows a good selectivity for cerium(III) with respect to alkali, alkaline earth, some transition and rare earth metal ions that are normally present along with cerium in its ores. The proposed sensor was investigated in partially non-aqueous media using acetone, methanol and DMSO mixtures with water. The electrode was further used as an indicator electrode for the potentiometric titration of Ce(III) solution against oxalic acid solution.